2022
DOI: 10.1002/fbe2.12010
|View full text |Cite
|
Sign up to set email alerts
|

Perturbing electron carriers of green algae Chlamydomonas reinhardtii for efficient physiological and metabolic regulation

Abstract: Microalgae are widely used in the field of food bioengineering. There are relatively few studies on the synthesis of intracellular electron carriers in microalgae and their related metabolic effects. In this study, overexpression of Geranyl diphosphate: 4-hydroxybenzoate geranyltransferase (lepgt), and the addition of 4-hydroxybenzoic acid (4-HB) as quinone ring precursor were adopted to regulate intracellular plastoquinone (PQ) and ubiquinone (UQ) levels in model algae Chlamydomonas reinhardtii. Small changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In addition, knockdown of CrPsbA that is a key component of photosystem II complex through artificial miRNA efficiently increased hydrogen bioproduction (Li et al, 2018). Interestingly, a recent study showed starch synthesis in C. reinhardtii could be effectively promoted by perturbation on electron carriers (Zhou et al, 2022). Particularly, in-depth study of the energy metabolism and a comprehensive understanding of cell cycle are helpful for the improvement of the growth rate and the cell density.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, knockdown of CrPsbA that is a key component of photosystem II complex through artificial miRNA efficiently increased hydrogen bioproduction (Li et al, 2018). Interestingly, a recent study showed starch synthesis in C. reinhardtii could be effectively promoted by perturbation on electron carriers (Zhou et al, 2022). Particularly, in-depth study of the energy metabolism and a comprehensive understanding of cell cycle are helpful for the improvement of the growth rate and the cell density.…”
Section: Introductionmentioning
confidence: 99%